The effect of social networks on academic self-handicapping with the mediating role of self-regulatory learning strategies and academic achievement among EFL students - Izadpanah, Siros; Charmi, Mahdis (Frontiers in Psychology, 2022)
Introduction In the academic context, social networking sites (SNSs) have reshaped the way university students connect and communicate with each other and the way they learn, thus influencing their identities and dimensions. This research investigates the effect of social networks on academic self-handicapping with the mediating role of self-regulatory and academic achievement. Method The current study is considered to be quantitative research in terms of its nature, applied research in terms of its purpose, and correlational descriptive one in terms of its method. The statistical population of the present study includes all language students of Tabriz University, whose number was 540 people. Sampling was done by the random sampling method. Using Morgan’s table, the sample size was estimated to be 225 people in 2022. Due to the possibility of falling, 10% was added to this number, and 250 questionnaires were distributed among 250 participants; 17 questionnaires were incomplete, and a total of 233 valid questionnaires were examined. Four questionnaires were administered to collect data. SPSS 26 and AMOS 24 software were used to analyze the collected data from questionnaires. Descriptive, inferential, and Structural Covariance Matrix (SEM) statistics were conducted to explore the effect of social networks on these variables. Results Findings showed that social networks significantly impact self-handicapping in language students of Tabriz University. 2- Social networks have a significant impact on self- self-handicapping with a mediating role of self-regulation learning strategies in language students of Tabriz University. 3- Social networks significantly affect self-handicapping, mediating role in language students’ academic progress at Tabriz University. Discussion Further investigation and experimentation into social networks are strongly recommended. In addition, studies show that self-handicapping is successful in helping individuals divert the assessments of others from attributing weak abilities to failure. Because self-handicapping behavior undermines achievement and can lead to long-term withdrawal from activities (such as school and college), parents and teachers must discourage self-handicapping and avoid behavior that may encourage it.